Marketing Politik Pemilukada Cagub Provinsi Bengkulu Tahun 2020 (Studi Pada Pasangan Helmi – Dedi) - Eka Patrisia, Novliza; Yuliani, Hafri (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
This paper is a result of the analysis and observations that the researchers conducted directly and openly. This research was carried out continuously by looking at several aspects related to the promotion of candidates as participants in the 2020 Bengkulu Provincial Election for Cagub. In this case the researchers focused on political marketing used by the number 1 pair, Helmi-Dedi. The research method used is the constructivist paradigm. Based on the results of research on political marketing applied by candidate pairs Helmi -Dedy in the Regional Head Election for the 2018-2023 period using an analysis knife, namely the Political Marketing Theory of Adnan Nursal (Nursal, 2004: 242) has three target groups that can be grouped into three: 1. Direct marketing of political products to potential voters (push political marketing), 2. Marketing of political products through mass media (pull political marketing) and 3. through influential groups, figures or organizations (pass political marketing).